Developmental programming of the neuroendocrine axis by steroid hormones: Insights from the sheep model of PCOS - Gurule, Sara; Sustaita-Monroe, Jessica; Padmanabhan, Vasantha; Cardoso, Rodolfo (Frontiers in Endocrinology, 2023)
The reproductive neuroendocrine system is a key target for the developmental programming effects of steroid hormones during early life. While gonadal steroids play an important role in controlling the physiological development of the neuroendocrine axis, human fetuses are susceptible to adverse programming due to exposure to endocrine disrupting chemicals with steroidal activity, inadvertent use of contraceptive pills during pregnancy, as well as from disease states that result in abnormal steroid production. Animal models provide an unparalleled resource to understand the effects of steroid hormones on the development of the neuroendocrine axis and their role on the developmental origins of health and disease. In female sheep, exposure to testosterone (T) excess during fetal development results in an array of reproductive disorders that recapitulate those seen in women with polycystic ovary syndrome (PCOS), including disrupted neuroendocrine feedback mechanisms, increased pituitary responsiveness to gonadotropin-releasing hormone (GnRH), luteinizing hormone (LH) hypersecretion, functional hyperandrogenism, multifollicular ovarian morphology, and premature reproductive failure. Similar to a large proportion of women with PCOS, these prenatally T-treated sheep also manifest insulin resistance and cardiovascular alterations, including hypertension. This review article focuses on the effects of prenatal androgens on the developmental programming of hypothalamic and pituitary alterations in the sheep model of PCOS phenotype, centering specifically on key neurons, neuropeptides, and regulatory pathways controlling GnRH and LH secretion. Insights obtained from the sheep model as well as other animal models of perinatal androgen excess can have important translational relevance to treat and prevent neuroendocrine dysfunction in women with PCOS and other fertility disorders.